AUTENTIKASI TUNA STEAK KOMERSIAL DENGAN METODE PCR-SEQUENCING - Asadatun Abdullah; . Nurjanah; Nanang Kurnia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Tuna is one of the  shery commodities which are susceptible to mislabeling and substituted with similarspecies, but lower price. Consumer as a purchaser will incur a loss (economical fraud) so it is needed a way toovercome these problems. This study aimed to optimized extraction of DNA obtained from the tuna and tunaexporter companies of modern markets, identi cation of DNA-based species-speci c primers with a target genecyt b, and characterization of DNA tuna authentication results. This study consisted of several steps beginning with the characterization of tuna, DNA extraction using CTAB method and Vivantis kit, ampli cation by PCR, electrophoresis, and nucleotide sequencing. The samples tested were successfully extracted and ampli ed with the appropriate size of 750 base pairs. PCR sequencing using cyt b gene targets resulted in the identi cation of tuna raw material. PCR sequencing of the nucleotide sequence of results which have been  tted to the NCBI data, which does not show any fraud in the form of substitution with other species. Species of yellow  n (Thunnus albacore), Albacore (Thunnus alalunga), big eye (Thunnus obesus) and blue  n (Thunnus macoyyi) has the highest homology i.e 99%, 99%, 99%, 100%, respectively.Keywords: authentication, cyt b, mt-DNA, PCR, tuna’s steaks